Gender differences in child/adolescent personality traits - Zupančič, Maja (Psihološka obzorja (Ljubljana), 2008)
The present study compared gender differences in parental perceptions of child personality trait expression across different age groups in Slovenia and Russia. The patterns of gender differences in adolescents were further explored using parent and self-rating methods of assessment. Employing the Inventory of Child Individual Differences (Halverson et al., 2003) reports on large samples of children/ adolescents (2 to 15 years) in both countries were obtained. Gender differences were small and similar across countries, and their patterns were closer to each other for the same data source across countries than they were for the two sources of information within the country. The parents in both countries concurred in rating daughters as somewhat more achievement orientated, compliant, considerate, and organized, whereas sons were assessed as slightly more active, antagonistic, and distractible. At the higher-order trait level, girls were perceived to be more conscientious and agreeable relative to the boys, especially from middle childhood onwards. Regarding self-reports, adolescent girls also scored significantly higher on Considerate and Positive Emotions scales than boys, while the former reported on higher agreeableness relative to the latter in Slovenia only. Gender differences were evident even in parental assessments of the youngest group but they did not systematically increase over children's age.
Keywords: osebnost; personality; razlike med spoloma; mladostniki; otroci; child; medkulturne razlike